2019
DOI: 10.1177/1042258719879674
|View full text |Cite
|
Sign up to set email alerts
|

Combining Internal and External R&D: The Effects on Innovation Performance in Family and Nonfamily Firms

Abstract: We examine the effect of combining internal and external R&D loci on innovation performance in family firms (FF) and nonfamily firms (non-FFs). Our longitudinal analysis of 27,438 firm-year observations of Spanish manufacturing firms from 1990 to 2016 shows that FFs can better exploit the benefits of simultaneously engaging in internal and external R&D activities, leading to a positive effect on innovation performance. Moreover, the relationship between combined internal and external R&D and innova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 137 publications
(212 reference statements)
7
72
0
1
Order By: Relevance
“…However, Duran et al (2016) found that when the CEO is the founder, innovation input increases and innovation output decreases, yielding a less efficient input-to-output conversion ratio. Additionally, concerning innovation differences, family firms are effective at simultaneously exploiting internal and external R&D, yet innovation performance variation depends, in part, on the firm's economic performance (Muñoz-Bullón et al, 2020). These, and an array of other effects, such as long-term orientation, create notable variation in innovation outcomes (Werner et al, 2018).…”
Section: Quadrant Iv: Shorter-term and Less Family-centered Themes Entrepreneurial Behaviormentioning
confidence: 99%
“…However, Duran et al (2016) found that when the CEO is the founder, innovation input increases and innovation output decreases, yielding a less efficient input-to-output conversion ratio. Additionally, concerning innovation differences, family firms are effective at simultaneously exploiting internal and external R&D, yet innovation performance variation depends, in part, on the firm's economic performance (Muñoz-Bullón et al, 2020). These, and an array of other effects, such as long-term orientation, create notable variation in innovation outcomes (Werner et al, 2018).…”
Section: Quadrant Iv: Shorter-term and Less Family-centered Themes Entrepreneurial Behaviormentioning
confidence: 99%
“…In addition, as far as a decision to pursue an external R&D investment is determined by the antecedent decision to invest in R&D internally (Piga and Vivarelli, 2004), we also need to understand which type of CG mechanisms are conducive or detrimental to internal R&D investments. We also encourage future research to investigate how CG might affect the combination of internal and external R&D (Muñoz‐Bullon et al, 2019). Therefore, future CG‐R&D investment research could highly benefit from examination of the effects of firm‐ and country‐level CG on different types of R&D investments and their combination.…”
Section: Implications Contributions Limitations and Future Researchmentioning
confidence: 99%
“…Social capital is defined by Bourdieu (1986: 248) as "the sum of real or potential resources linked to the possession of a lasting network of relations of knowledge and mutual recognition." It is considered a key element for strategic collaborations, increasing the probability of successful collaborations due to the trust and willingness to share resources among the partners (Hitt, Ireland, Camp, and Sexton, 2001;Nahapiet and Ghoshal, 1998;Siebert, Kraimer, and Liden, 2001). In this sense, Galán and Castro (2004: 108) pointed out that "confidence can lead to joint efforts and, for this reason, it is considered as an antecedent and an extraordinary lubricant of collaboration."…”
Section: Collaborative Innovation Conceptualizationmentioning
confidence: 99%
“…Innovation is fundamentally a collaborative effort between people who share ideas, perspectives, and values (Adler and Kwon, 2002). That is why social capital, understood as the set of values, norms, and attitudes that foster collaborative dynamics is a resource that favors the exchange of knowledge and information (Nahapiet and Ghoshal, 1998), as well as innovation processes (Sánchez-Famoso, Iturralde, and Maseda, 2015). The family business, given its peculiar characteristics linked to the family with solid business values and strong social ties (Hall, Melin, and Nordqvist, 2001), are companies with essential reserves of social capital in which interand intra-organizational relations have a strong influence on their behavior and dynamics (Sánchez-Famoso, Maseda, and Iturralde, 2017).…”
Section: Intra-organizational Behaviormentioning
confidence: 99%
See 1 more Smart Citation